Corrosion study of ZrN deposited on 304L stainless steel. (1st May 2013) - Ningshen, S; Gupta, R K; Kamal, S; Chawla, V; Chandra, R; Mudali, U K
<x xml:space="preserve">Abstract</x> The ZrN films were deposited on type 304L stainless steel using dc magnetron sputtering technique at different substrate temperatures from room temperature up to 600°C. The ZrN films have been analysed for their composition, microstructure, surface morphology and their corrosion resistance in different nitric acid concentrations. The grazing incidence angle X-ray diffraction analysis showed the texture orientation of (111) or (200) plane depending on the substrate temperature. The atomic force microscopy analysis reveals the formation of ZrN agglomerates with no visible cracks or pores. However, increase in grain size (10-20 nm) and roughness (10-50 nm) with increase in the substrate temperature was observed. The potentiodynamic polarisation and electrochemical impedance spectroscopy results indicated that the corrosion resistance of different ZrN films, although high in 1 mol L−1 HNO3, suffered a marked decrease in 8 mol L−1 HNO3 concentration.